2021
DOI: 10.3390/met12010010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Metallography Study of the Oxidation at 1250 °C of {Co+Ni}-Based Superalloys Containing Ti to Form MC Carbides

Abstract: Six conventionally cast chromium-rich titanium-containing alloys based on cobalt and nickel with various Co/Ni ratios were considered. They were tested in oxidation in air at 1250 °C for 70 h in a thermo-balance. The mass gain curves were exploited to specify different types of kinetic constants as well as several parameters characterizing the oxide spallation occurring during cooling. The obtained results show that, the higher the Ni content, the slower the mass gain and the better the quality of the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…By isolating chromia a little from the air during the oxidation tests, it can be thought that chromia volatilization was thus a little prevented, as this was recently encountered with a TiO 2 developed on the outer side of chromia for Co and Ni alloys containing Ti. [ 33 ] The degradation of the Ni‐richest alloys of this study by oxidation was not significantly worse than in the case of the oxidation‐resistant Ni–30Cr alloy taken in reference. There are only a limited deleterious role of Ta and no real effect of the added Co.…”
Section: Discussionmentioning
confidence: 72%
“…By isolating chromia a little from the air during the oxidation tests, it can be thought that chromia volatilization was thus a little prevented, as this was recently encountered with a TiO 2 developed on the outer side of chromia for Co and Ni alloys containing Ti. [ 33 ] The degradation of the Ni‐richest alloys of this study by oxidation was not significantly worse than in the case of the oxidation‐resistant Ni–30Cr alloy taken in reference. There are only a limited deleterious role of Ta and no real effect of the added Co.…”
Section: Discussionmentioning
confidence: 72%
“…It is well known that oxidation resistance is one of the most important aspects of nickel-based superalloys since poor oxidation resistance hinders their possible applications at high temperatures [12]. The oxidation behaviors of advanced nickel-based superalloys at temperatures higher than 700 • C have been studied extensively [19][20][21][22]. Brenneman et al [19] studied the oxidation behavior of GTD111 superalloy at 900 • C in air and concluded that the oxidation resistance was provided by the continuous dense Cr 2 O 3 oxide band, rather than the discontinuous Al 2 O 3 oxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [23] studied the oxidation behavior of single-crystal nickel-based superalloy DD32 in air at 900 • C and 1000 • C and found that two oxidation steps appeared in the oxidation kinetics, which were controlled by NiO growth and Al 2 O 3 growth, respectively. Berthod et al [20] studied the oxidation behavior of six (Co + Ni)-based Cr-rich alloys with different Co/Ni ratios at 1250 • C and concluded that the higher the Ni content, the better the oxidation resistance of the alloys. Moffat et al [21] studied the oxidation behavior of a carbide network in low or high carbon Co-based superalloys at 1000 • C. They concluded that the carbide in low carbon alloys is more soluble than that in high carbon alloys, thus reducing the continuity of the carbide network and ultimately leading to an increase in the thickness of the oxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…Among them there are applications that combine the complex geometry of the concerned components (excluding single crystals and oxide dispersion strengthened superalloys), the need of high resistance against corrosion by hot aggressive melts in absence of protective coatings (excluding alumina-forming superalloys), sustainability of the reinforcing particles even at 1100 • C and slightly more (excluding γ -reinforced alloys), and not too high density (excluding heavy refractory alloys). The reinforcement of cobalt-based [1,2,7] and nickel-based [4,8,9] conventionally cast chromium-rich alloys with MC carbides such as TaC, HfC or TiC is one of the ways new developments and application prospects to superalloys of this family are offered. The refractory monocarbides list can be enriched by ZrC, which may be present in solidified alloys with a morphology similar to the MC carbides cited above [10].…”
Section: Introductionmentioning
confidence: 99%